Simplified Method for the Purification of Group A Streptococcal M-Proteins: Solution of the Multiple Banding Problem - Straus, David C. (1974)
A simple and rapid procedure for the isolation in high yield (about a 30% recovery based on the total 30 to 60% ammonium sulfate recovery) of homogeneous purified group A streptococcal M-protein is described. M-proteins extracted from whole cells of group A streptococci by treatment with hot HCl were neutralized, fractionated with ammonium sulfate, dialyzed, lyophilized, and then subjected to treatment with hot 60% trichloroacetic acid. This was shown to produce an M-protein preparation, free of group A carbohydrate activity and extraneous antigens, in yields up to 10-fold higher than previous methods in about one-fifth the time. These M-protein preparations were shown to: (i) have similar amino acid compositions to their respective type-specific proteins purified by diethylaminoethyl and O-(carboxymethyl) cellulose chromatography, (ii) react with their respective type-specific antisera in Ouchterlony diffusion, (iii) produce antisera in rabbits capable of promoting streptococcal long-chain formation in vitro, and (iv) give only one major band on polyacrylamide gel disk electrophoresis. The data allow for an explanation of the hitherto described multiple banding M-proteins seen on acrylamide electrophoresis.